Fetoscopic laser ablation of placental anastomoses in twin–twin transfusion syndrome using 'Solomon technique'. (2nd September 2013) - Ruano, R.; Rodo, C.; Peiro, J. L.; Shamshirsaz, A. A.; Haeri, S.; Nomura, M. L.; Salustiano, E. M. A.; de Andrade, K. K.; Sangi‐Haghpeykar, H.; Carreras, E.; Belfort, M. A.
ABSTRACT Objective To document perinatal outcomes following use of the 'Solomon technique' in the selective photocoagulation of placental anastomoses for severe twin–twin transfusion syndrome (TTTS). Methods Between January 2010 and July 2012, data were collected from 102 consecutive monochorionic twin pregnancies complicated by severe TTTS that underwent fetoscopic laser ablation at four different centers. We compared outcomes between subjects that underwent selective laser coagulation using the Solomon technique (cases) and those that underwent selective laser coagulation without this procedure (controls). Results Of the 102 pregnancies examined, 26 (25.5%) underwent the Solomon technique and 76 (74.5%) did not. Of the 204 fetuses, 139 (68.1%) survived up to 30 days of age. At least one twin survived in 82 (80.4%) pregnancies and both twins survived in 57 (55.9%) pregnancies. When compared with the control group, the Solomon‐technique group had a significantly higher survival rate for both twins (84.6 vs 46.1%; P < 0.01) and a higher overall neonatal survival rate (45/52 (86.5%) vs 94/152 (61.8%); P < 0.01). Use of the Solomon technique remained independently associated with dual twin survival (adjusted odds ratio (aOR), 11.35 (95% CI, 3.11–53.14); P = 0.0007) and overall neonatal survival rate (aOR, 4.65 (95% CI, 1.59–13.62); P = 0.005) on multivariable analysis. There were no cases of recurrent TTTS or twin anemia–polycythemia sequence (TAPS) in the Solomon‐technique group. Conclusions Use of the Solomon technique following selective laser coagulation of placental anastomoses appears to improve twin survival and may reduce the risk of recurrent TTTS and TAPS. Our data support the idea of performing a randomized controlled trial to evaluate the effectiveness of the Solomon technique. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.